Evaluasi Program Keluarga Harapan Kelurahan Sidotopo Kota Surabaya - Anggita Nanda Ayu Kusuma; Levina Linadi; Karina Putri Wahyudin; Melanika Netta Anggraini; Galuh Refal Tianta; Tauran Tauran; Wilda Sumarsyah (Universitas 17 Agustus 1945, 2026)
Poverty in Indonesia remains an unresolved social problem and poses a structural challenge to the government. Improving the quality of life of vulnerable communities requires deeper intervention. Therefore, to assist and improve the quality of life of vulnerable communities, the government has launched various assistance programs, one of which is the Family Hope Program (PKH). The Family Hope Program (PKH) is present not only to support the community's economy but also encourages behavioral changes in PKH beneficiaries, particularly in the context of children's education, maternal and toddler health, and protection for vulnerable groups. This program is implemented in various areas of Surabaya City, one of which is the Sidotopo Village, Semampir. In this area, there are still underprivileged groups. The PKH program has significantly assisted beneficiaries in the Sidotopo area in improving their socio-economic welfare. The purpose of this evaluation is to describe the implementation of PKH in terms of effectiveness, equity, targeting accuracy, and the impact of program implementation on beneficiaries in the Sidotopo area. This evaluation uses data collection techniques based on observations and interviews with PKH mentors and PKH beneficiaries in the Sidotopo Village, as well as documentation studies. Based on the research results, it is clear that the implementation of the Family Hope Program (PKH) in Sidotopo has been effective, equitable, and well-targeted in improving the welfare of its residents. This is evident in the decline in poverty rates and increased access to education and healthcare.